AN ANALYTICAL GRAMMATICAL STUDY OF THE INDECLINABLE POEMS: THE SCIENTIFIC CAUSE IN THE DIWAN OF AHMED SHAWQI- PART ONE AS MODEL - Ibrahim, Hawa; Sulaiman, Khalida (Humanities Journal of University of Zakho, 2025)
After grammar the second level of language in terms of linguistic study. The importance of this study comes from the fact that it relates to the study of Quranic grammar. Which is considered the most eloquent. Highest and most sublime text ever .After it in eloquence and sublimity comes Arabic poetry. Which we have made a model for our study and we devoted a part of it to the collection of poems of one of the greatest poets of the Arab world in various eras. Namely the poet “Ahmed Shawqi”. Who was pledged allegiance to by the writers and poets of his time as the Emir of poetry so he was nicknamed (the Emir of poets). He had a unique poetic talent and a flowing spring finding no difficulty in composing poetry .And his poetic production reached what almost no ancient or modern Arab poet reached. So he was the reason for our choosing his collection to be a model for the study. The study was limited to the first part of his collection of poems of “Ahmed Shawqi” due to its breadth and the abundance of nouns that are prohibited from being declined in it . And due to the large number of reasons being prohibited from being declined. Which amount to nine reasons. I dealt only with the scientific reason for being prohibited from being declined. Which in turn is divided into six reasons. Which are: Knowledge with foreignness knowledge with feminine. Knowledge with the increase of alif and nun. Knowledge with the weight of the verb. Knowledge with justice. And knowledge with mixed composition. We explained these reason. Which are divided in to sections. And we touched on the opinions of some grammarians on them and on their head is “Sibawayh”. We defined the methodology followed in the study. Which is the inductive method by tracing the linquistic phenomenon in the first part of the diwan of “Ahmed Shawqi” . We also used an analytical method by analyzing the indeclinable words according to the six schools of thought associated with the scientific method. We concluded the research with a conclusion in which we explained the most important results we reached through induction in the poems of.